2021
DOI: 10.1182/blood-2021-148723
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Teclistamab in Combination with Daratumumab for the Treatment of Patients with Relapsed/Refractory Multiple Myeloma: Results from a Phase 1b Multicohort Study

Abstract: Introduction: Teclistamab (Tec) is a B-cell maturation antigen × CD3 T-cell redirecting bispecific antibody. In the phase 1 MajesTEC-1 trial in patients (pts) with heavily pretreated relapsed/refractory multiple myeloma (RRMM), Tec monotherapy was well tolerated and yielded an overall response rate of 65% and very good partial response or better rate of 58% at the recommended phase 2 dose (RP2D) with 6.1 months' median follow-up; responses were durable and deepened over time. Daratumumab (Dara) is a monoclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…101,102 Combination therapy incorporating teclistamab is ongoing and preliminary results have shown promising results. 103 Elranatamab, (PF-06863135), a humanized bispecific molecule that targets BCMA expressed on MM and engages CD3 on T cells, is being studied in phase 1 study MagnetisMM-1 as monotherapy, and also as combination therapy with lenalidomide and pomalidomide.…”
Section: Bispecific Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…101,102 Combination therapy incorporating teclistamab is ongoing and preliminary results have shown promising results. 103 Elranatamab, (PF-06863135), a humanized bispecific molecule that targets BCMA expressed on MM and engages CD3 on T cells, is being studied in phase 1 study MagnetisMM-1 as monotherapy, and also as combination therapy with lenalidomide and pomalidomide.…”
Section: Bispecific Antibodiesmentioning
confidence: 99%
“…The phase 1/2 MajesTEC‐1 trial in triple‐class exposed RRMM patients showed that at a median follow up of around 9 months, Teclistamab monotherapy achieved ORR of 64% (95% CI: 56–72), with a complete response or better achieved in 30% of pts, and with manageable safety profile 101,102 . Combination therapy incorporating teclistamab is ongoing and preliminary results have shown promising results 103 …”
Section: Current Treatment Paradigmmentioning
confidence: 99%
“…7 Daratumumab was shown to deplete CD38+ myeloid-derived suppressor cells, Bregs, and Tregs in vitro and promote T-cell clonal expansion, 40 and is now being studied in combination with teclistamab and talquetamab. 41,42 Initial data from these studies are promising but longer follow-up is needed, and cohorts with additional pomalidomide and dexamethasone are accruing.…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Overall, the combination was well tolerated with safety comparable with monotherapy. 52 Talquetamab is being studied as monotherapy and in combination with other agents in RRMM.…”
Section: Therapies In Relapsed Refractory Multiple Myelomamentioning
confidence: 99%